Current Strategies to Modify the Functional Properties of Proteins Extracted from Pumpkin Seeds: A Comprehensive Review - Vinay Kumar Pandey; Kriti Singh; Tejas Suthar; Shivangi Srivastava; Sarvesh Rustagi; Diána Ungai; Béla Kovács; Ayaz Mukarram Shaikh (Horticulturae)
The functional properties of pumpkin seed proteins remain unutilized in numerous food and industrial applications. Several current approaches aim to improve the functional properties of pumpkin seed proteins, allowing their innovative potential to develop and modify significantly. Several strategies can be implemented to alter the functional properties of proteins isolated from pumpkin seeds. The first is enzymatic hydrolysis, regardless of whether, proteases may free peptide binding and profoundly impact the protein structure and functionality. Thermal treatment can include heating and cooling to replace protein conformation and increase solubility, emulsification, and gelation properties. Chemical modification techniques, including acylation and glycation, can also be used to improve stability, viscosity, and foaming ability. Functional properties and, where possible, ingredients with many applications may include exceptional possibilities for proteins modified in food preparations, such as dairy replacements, plant-based meat analogues, and free gluten that have an outstanding aspect, satisfactory quality, and nutritional profiles. As multiple different proteins act as precursors of active peptides, they can also be used to generate bio-specific foods. This review briefly provides information about various types of protein extraction techniques and functional properties that are modified by different types of processing technologies.